Landslide Disaster Risk Assessment Model in Soppeng Regency, South Sulawesi - Adi Maulana; Suharman Hamzah; Iswandi Utama; Jamal Rauf Husain (EPI International Journal of Engineering, 2019)
Landslide disaster risk assessment model has been proposed for Soppeng Regency which is located in the central part of South Sulawesi Province. Some areas in this regency are classified as landslide prone area based on its geological condition. This study is aimed to assess the landslide vulnerability level and produce a landslide vulnerability map by using mapping method as a basis to model the risk reduction assessment. The component of disaster risk assessment consists of threats, vulnerabilities, and capacities. These components are used to obtain the level of disaster risk in an area by calculating the potential for exposed lives, loss of property and environmental damage. The result shows that Soppeng Regency region has some areas that are prone to landslides with low-high levels. The Vulnerability Assessment is classified as medium level whereas the result of landslide disaster capacity assessment is also shown as medium level. Based on these analyses, it was concluded that Soppeng Regency had a high landslide threat index, with a medium exposed population index and a medium capacity index. The study of landslide disaster risk assessment in Soppeng Regency has shown that Soppeng Regency has been classified as landslide prone area with the medium risk level, especially in mountainous and river bank area. It is recommended that disaster risk assessment model should be used as one of the references for providing disaster risk mitigation plan in disaster risk reduction program.